Advantages and applications of CAR-expressing natural killer cells - Glienke, Wolfgang; Esser, Ruth; Priesner, Christoph; Suerth, Julia D.; Schambach, Axel; Wels, Winfried S.; Grez, Manuel; Kloess, Stephan; Arseniev, Lubomir; Koehl, Ulrike (Frontiers in Pharmacology, 2015)
In contrast to donor T cells, natural killer (NK) cells are known to mediate anti-cancer effects without the risk of inducing graft-versus-host disease (GvHD). In order to improve cytotoxicity against resistant cancer cells, auspicious efforts have been made with chimeric antigen receptor (CAR) expressing T- and NK cells. These CAR-modified cells express antigen receptors against tumor-associated surface antigens, thus redirecting the effector cells and enhancing tumor-specific immunosurveillance. However, many cancer antigens are also expressed on healthy tissues, potentially leading to off tumor/ on target toxicity by CAR-engineered cells. In order to control such potentially severe side effects, the insertion of suicide genes into CAR-modified effectors can provide a means for efficient depletion of these cells. While CAR-expressing T cells have entered successfully clinical trials, experience with CAR-engineered NK cells is mainly restricted to pre-clinical investigations and predominantly to NK cell lines. In this review we summarize the data on CAR expressing NK cells focusing on the possible advantage using these short-lived effector cells and discuss the necessity of suicide switches. Furthermore, we address the compliance of such modified NK cells with regulatory requirements as a new field in cellular immunotherapy.